ANALISIS PENDAPATAN USAHATANI KOPI DI DESA BONTO TENGNGA KECAMATAN SINJAI BORONG KABUPATEN SINJAI - Nisa, Nur Haerun; Nurdin, Fadilah; Nurwadiah, Nurwadiah; Darmawan, A. Muh Alfian; Wahyuningsih, Wahyuningsih (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2024)
The global popularity and fascination with coffee is mainly due to its unique flavor and is supported by historical, traditional, social and economic interests. This research aims to determine the income of coffee farming in Bonto Tengnga Village, Sinjai Borong District, Sinjai Regency. The data used is primary data and secondary data. This research uses data collection techniques by direct observation using questionnaires. The sample was determined using simple random sampling by taking a sample of 30 farmers. The data analysis used is descriptive analysis. The research results show that the income of coffee farmers in Bonto Tengnga Village is IDR. 2,362,000, profitable and feasible because the income obtained is higher than the costs borne by farmers. The R/C value of coffee farming is more than 1, namely 3.8.